Beneficial Effects of Long-Term Administration of an Oral Formulation of Angiotensin-(1–7) in Infarcted Rats - Fúlvia D. Marques; Marcos B. Melo; Leandro E. Souza; Maria Claúdia C. Irigoyen; Rúben D. Sinisterra; Frederico B. de Sousa; Sílvia Q. Savergnini; Vinícius B. A. Braga; Anderson J. Ferreira; Robson A. S. Santos (International Journal of Hypertension)
In this study was evaluated the chronic cardiac effects of a formulation developed by including angiotensin(Ang)-(1–7) in hydroxypropyl β-cyclodextrin (HPβCD), in infarcted rats. Myocardial infarction (MI) was induced by left coronary artery occlusion. HPβCD/Ang-(1–7) was administered for 60 days (76 μg/Kg/once a day/gavage) starting immediately before infarction. Echocardiography was utilized to evaluate usual cardiac parameters, and radial strain method was used to analyze the velocity and displacement of myocardial fibers at initial time and 15, 30, and 50 days after surgery. Real-time PCR was utilized to evaluate the fibrotic signaling involved in the remodeling process. Once-a-day oral HPβCD/Ang-(1–7) administration improved the cardiac function and reduced the deleterious effects induced by MI on TGF-β and collagen type I expression, as well as on the velocity and displacement of myocardial fibers. These findings confirm cardioprotective effects of Ang-(1–7) and indicate HPβCD/Ang-(1–7) as a feasible formulation for long-term oral administration of this heptapeptide.